Effector-Mining in the Poplar Rust Fungus Melampsora larici-populina Secretome - Lorrain, Cécile; Hecker, Arnaud; Duplessis, Sébastien (Frontiers in Plant Science, 2015)
The poplar leaf rust fungus, Melampsora larici-populina has been established as a tree-microbe interaction model. Understanding the molecular mechanisms controlling infection by pathogens appears essential for durable management of tree plantations. In biotrophic plant parasites, effectors are known to condition host cell colonization. Thus, investigation of candidate secreted effector proteins is a major goal in the poplar-poplar rust interaction. Unlike oomycetes, fungal effectors do not share conserved motifs and candidate prediction relies on a set of a priori criteria established from reported bona fide effectors. Secretome prediction, genome-wide analysis of gene families and transcriptomics of M. larici-populina have led to catalogues of more than a thousand secreted proteins. Automatized effector mining pipelines hold great promise for rapid and systematic identification and prioritization of candidate secreted effector proteins for functional characterization. In this review, we report on and discuss the current status of the poplar rust fungus secretome and prediction of candidate effectors in this species.